Working capital management and its impact on profitability- a study on Glaxo SmithKline Bangladesh ltd. - Chowdhury, Amir Obaidul Huq (BRAC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2017.